Investigating the ability of Stardust capture media to preserve collected particles intact - Foster, N.; Wozniakiewicz, P.; Kearsley, A.; Burchell, M.; Cole, M.; Bland, Phil (E D P Sciences, 2010)
We briefly summarise our ongoing efforts to evaluate the success of cometary particle capture by NASA's Stardust mission. We demonstrate the use of a variety of analysis techniques to investigate the state of preservation in laboratory analogues of the Stardust encounter at 6.1 km s-1, using well characterised projectiles and flight grade foils and aerogel.